El material concreto en el aprendizaje de las operaciones de suma y resta en Educación General Básica - Caraguay Valencia, Isabel María (2023)
In the Curricular Integration work, the general objective was: To determine the incidence of concrete material in the learning of addition and subtraction operations in students of third grade parallel "C" of the School of Basic General Education "Alonso de Mercadillo" during the academic period 2022 - 2023, likewise, it has specific objectives; To diagnose the level of learning in the resolution of addition and subtraction operations in students of third grade of Basic General Education; To design a didactic guide to strengthen the learning of addition and subtraction operations in students of third grade of Basic General Education; To evaluate the incidence of the use of concrete material in the learning of addition and subtraction operations in students of third grade of Basic General Education; Methods used in this research helped to direct the present work and based on them, infer criteria on the subject was raised. It was carried out under a mixed qualitative-quantitative approach of a descriptive, non-experimental and statistical type with the reality of the research problem. The following techniques were used: direct observation, interview and diagnostic test, as well, the population consisted of 27 students and a teacher, given this, it was determined that the use of concrete materials in practice, during the development of a class, are beneficial. For which, it is concluded that the use of concrete material in the subject of mathematics contributes significantly to the learning of addition and subtraction operations, thus, students develop their creativity and imagination. Keywords: mathematics, concrete material, basic operations, learning, education.